Book Review: The Revelations of a Living Legend. The Memoirs of Dr. Errington Washington Isaac Watkins Sr. - Walker, Berthamae L. (International Journal of Bahamian Studies, 2015)
The Revelations of a Living Legend. The Memoirs of Dr. Errington Washington Isaac Watkins Sr.